2020
DOI: 10.1016/j.appet.2020.104812
|View full text |Cite
|
Sign up to set email alerts
|

Using consumption and reward simulations to increase the appeal of plant-based foods

Abstract: The production of meat is a main contributor to current dangerous levels of greenhouse gas emissions. However, the shift to more plant-based diets is hampered by consumers finding meatbased foods more attractive than plant-based foods. How can plant-based foods best be described to increase their appeal to consumers? Based on the grounded cognition theory of desire, we suggest that descriptions that trigger simulations, or re-experiences, of eating and enjoying a food will increase the attractiveness of a food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 64 publications
(72 reference statements)
2
36
1
Order By: Relevance
“…Flavonoids are secondary plant metabolites that are consumed through vegetables, fruits, teas, wines, propolis, medicinal plants, and so on. These compounds aid organoleptic characteristics of foods (e.g., color and taste of tea and wine) and are of interest due to biological properties affecting human health [ 1 , 2 ]. As non-essential nutrients, they have received much attention in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are secondary plant metabolites that are consumed through vegetables, fruits, teas, wines, propolis, medicinal plants, and so on. These compounds aid organoleptic characteristics of foods (e.g., color and taste of tea and wine) and are of interest due to biological properties affecting human health [ 1 , 2 ]. As non-essential nutrients, they have received much attention in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the sixth hypothesis considered for this study is confirmed, a higher level of income generates more appreciation for the quality of the purchased vegetables than their price or available offers. In this case, presenting the sustainable vegetables as of higher quality through specific labeling would offer the consumers the option of easily identifying them in stores or markets and, therefore, satisfy their need for quality purchases while having a sustainable diet, an idea that correlates with previous studies [85,101].…”
Section: Resultsmentioning
confidence: 82%
“…Additionally, through their studies, they propose alternatives to the current consumption patterns. For example, sustainable diets [3], change of language on vegetable product labels into a more stimulating one [85], plant-based and oat-based protein consumption [22], or food education for children and parents [6,86], therefore aiming at the health aspect of a sustainable food choice [87].…”
mentioning
confidence: 99%
“…Labeling healthy foods with words that refer to sensory characteristics (e.g., sweet and tangy) increased taste expectations and healthy choices, compared to labeling the same foods with health features (e.g., vitamin-rich and protein-packed; [27, 28]). These effects seem to be driven by increased eating simulations, as was shown in experiments manipulating the labels for meat-based and plant-based foods [29]. Here, food descriptions that contained words referring to sensory, hedonic, and eating context features increased eating simulations and perceived attractiveness of both plant-based and meat-based foods, compared to food descriptions that listed ingredients and visual features [29].…”
Section: A Grounded Cognition Approach To Desirementioning
confidence: 97%
“…These effects seem to be driven by increased eating simulations, as was shown in experiments manipulating the labels for meat-based and plant-based foods [29]. Here, food descriptions that contained words referring to sensory, hedonic, and eating context features increased eating simulations and perceived attractiveness of both plant-based and meat-based foods, compared to food descriptions that listed ingredients and visual features [29]. The effects of these simulation-based labels on food attractiveness were mediated by eating simulations (“I imagine what the food would taste and feel like”).…”
Section: A Grounded Cognition Approach To Desirementioning
confidence: 99%